2016
DOI: 10.1103/physrevaccelbeams.19.110702
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and long term operation of a novel superconducting undulator with 15 mm period length in a synchrotron light source

Abstract: A new cryogen-free full scale (1.5 m long) superconducting undulator with a period length of 15 mm (SCU15) has been successfully tested in the ANKA storage ring. This represents a very important milestone in the development of superconducting undulators for third and fourth generation light sources carried on by the collaboration between the Karlsruhe Institute of Technology and the industrial partner Babcock Noell GmbH. SCU15 is the first full length device worldwide that with beam reaches a higher peak field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Machine protection interlocks typically include beam loss monitoring and beam abort systems. For almost as long, but mostly in the past 10-12 years, superconducting magnets-SCUs [10,11], wigglers [23], and superbends [24]-have been employed for the generation of high-energy photons in electron synchrotron light sources. While all superconducting wigglers and SCUs have quench-detection interlocks to protect the magnet, very little has been written about characterizing and preventing beam-loss induced quenches.…”
Section: Quenchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine protection interlocks typically include beam loss monitoring and beam abort systems. For almost as long, but mostly in the past 10-12 years, superconducting magnets-SCUs [10,11], wigglers [23], and superbends [24]-have been employed for the generation of high-energy photons in electron synchrotron light sources. While all superconducting wigglers and SCUs have quench-detection interlocks to protect the magnet, very little has been written about characterizing and preventing beam-loss induced quenches.…”
Section: Quenchesmentioning
confidence: 99%
“…Magnetic simulations suggest that superconducting undulators (SCUs) outperform other undulator technologies in terms of undulator peak field B for a given period length and magnetic gap [1][2][3]. As a result, superconducting undulators have the potential to significantly boost the brightness of high-energy x-ray beams, and therefore attracting the interest of the light source community in developing this technology [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This 0.6-mm thickness will also be adopted for future SCUs at APS. At ANKA, a beam liner is used that allows for only a 1-mm difference between the vacuum and magnetic gaps [17].…”
Section: Computed Magnetic Fields Of Cryogenic Permanent Magnet Undulmentioning
confidence: 99%
“…For undulators based on the concept of wound coils, the advantage of using superconducting wires or tapes simply arises from the significantly increased current density and the reduction in resistive losses. So far, these concepts were mainly demonstrated with the use of LTS wires [2,3] whereas only a small number of research projects demonstrated undulator concepts with the use of HTS tapes and bulks [4,5].…”
Section: Introductionmentioning
confidence: 99%